SELF CARE ABILITY INFLUENCES THE QUALITY OF LIFE CONGESTIVE HEART FAILURE (CHF) PATIENTS - rizka febtrina; Elisa Mardika Putri; Eka Malfasari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
The prevalence of congestive heart failure sufferers in Indonesia is very high and is expected to continue to increase every year. Heart failure conditions and other manifestations cause a decrease in the quality of life due to the patient's inability to perform self-care properly. The purpose of this study was to determine the relationship between self-care ability and the quality of life of patients with congestive heart failure (CHF) in cardiac outpatient unit Arifin Achmad Hospital, Riau Province. This research was conducted on 64 respondents which by purposive sampling technique. Methode of this research was descriptive correlative with cross-sectional disign. The instrument of this research is the Self Care of Heart Failure Index (SCHFI) questionnaire to measure self-care ability and Minnesota Living with Heart Failure Questionnaire (MLHFQ) questionnaire to measure quality of life. The results of this study indicate that the respondent's self-care ability is balanced by good and bad as many as 32 respondents (50.0%) and the quality of life of the majority is bad as many as 39 respondents (60.9%). Based on the chi square test it can be concluded that p value= 0.01 (<0.05) means that there is a significant relationship between self-care ability and the quality of life of people with congestive heart failure (CHF). The recommendation for further research is to study about the factors that influence self-care ability and quality of life in patients with congestive heart failure.